2006
DOI: 10.1002/clc.4960291103
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibitors in post‐myocardial infarction cardiogenic shock—an update

Abstract: Summary: Cardiogenic shock (CS) in acute myocardial infarction, after successful coronary angioplasty, still carries a case fatality rate of 50%. These patients succumb to a systemic metabolic storm, superimposed on extensive myocardial necrosis and stunning. Nitric oxide (NO) overproduction contributes to the pathophysiology of this morbid state. Current data regarding the physiologic effects of NO and nitric oxide synthase (NOS) inhibitors on the cardiovascular system are reviewed. Clinical trials assessing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…As previously mentioned, CS induces a systemic inflammatory response, iNOS activation and excessive production of NO which reduces myocardial contractility, suppresses mitochondrial respiration, attenuates the β-adrenergic inotropic response and induces inadequate systemic vasodilation, leading to systemic hypoperfusion (Kaluski et al, 2006;Shpektor, 2010). The overproduction of peroxynitrite also aggravates myocardial contractile dysfunction (Kaluski et al, 2006;Pacher et al, 2007).…”
Section: Inducible Nitric Oxide Synthasementioning
confidence: 96%
See 1 more Smart Citation
“…As previously mentioned, CS induces a systemic inflammatory response, iNOS activation and excessive production of NO which reduces myocardial contractility, suppresses mitochondrial respiration, attenuates the β-adrenergic inotropic response and induces inadequate systemic vasodilation, leading to systemic hypoperfusion (Kaluski et al, 2006;Shpektor, 2010). The overproduction of peroxynitrite also aggravates myocardial contractile dysfunction (Kaluski et al, 2006;Pacher et al, 2007).…”
Section: Inducible Nitric Oxide Synthasementioning
confidence: 96%
“…Importantly, under inflammatory conditions, the reaction of NO with ROS is favored, originating RNS such as peroxynitrite (Pacher et al, 2007). Both excess NO and peroxynitrite can cause deleterious effects in the heart, namely cell apoptosis, contractile dysfunction, irreversible reduction of myocardial oxygen consumption and dysregulation of heart rate and rhythm (Cotton et al, 2002;Kaluski et al, 2006;Pacher et al, 2007). The overexpression of iNOS also appears to contribute to myocardial fibrosis and ventricular hypertrophy (Zhang et al, 2007).…”
Section: Inducible Nitric Oxide Synthasementioning
confidence: 99%
“…22 Because unexpectedly low systemic vascular resistance is often seen in the setting of cardiogenic shock, inflammatory and neurohormonal mediators have been speculated to play a role in the development and propagation of this clinical deterioration. [23][24][25] Inflammatory cytokines increase the expression of inducible nitric oxide synthase (NOS). This increases the levels of NO, thereby decreasing systemic vascular resistance and myocardial contractility.…”
Section: Therapymentioning
confidence: 99%
“…Initial small nonrandomized single-center studies of a nonselective NOS inhibitor showed improved hemodynamic parameters and 30-day mortality. 23,24 Subsequently, a larger international, multicenter, randomizedcontrolled, double-blind, placebo-controlled trial (TRIUMPH) evaluated the use of the NOS inhibitor L-n-monomethylarginine (L-NMMA), in post-MI cardiogenic shock patients who had undergone PCI. 25 This demonstrated a blood pressure improvement, but the study was discontinued early for failure to demonstrate a 30-day morality benefit.…”
Section: Therapymentioning
confidence: 99%
“…Cardiogenic shock is a state of inadequate tissue perfusion due to cardiac dysfunction, despite adequate left ventricular filling pressure. It is caused by extensive myocardial damage and appears to be aggravated by a systemic inflammatory response [3][4][5][6]. The result is hypotension with metabolic acidosis and often a fatal outcome.…”
Section: Introductionmentioning
confidence: 99%